BIODEGRADATION OF POLYURETAN RESULTS OF SYNTHESIS OF SOYBEAN OIL, GLYCOLOLY POLYOKYLETHLES, AND METHYLES-4,4’-DIFENILDIISOSIANAT - Rohaeti, Eli; Senam, Senam (Jurnal Penelitian Saintek, 2010)
The objective of research were to synthesize polyurethane from soybean oil, P EG400 and MDI, to determine the cross linking, and to learn the influence of incubation times toward degradability of polyurethane. Polyurethane was synthesized from soybean oil and oxydated soybean oil at room temperature followed by curing for 10 hours at 70 DC, and than at 100 "c for 3 hours. The synthesis was conducted with mass composition SBOI OSBO : P EG400 : MDI = 1 : 2 : 3. Biodegradation was conducted by using microorganism in an actived sludge of malka medium at 37°C. The variation of incubation times were 5, 10, 15, 20, 25, and 30 days, respectively with changes of media every 5 days. Characterizations of polyurethane were functional groups, cross linking, mass loss and biodegradability. The oxydated soybean oil has increased intensity of -OR functional group, hydroxyl number, density, melting and boiling point, otherwise the refraction index has decreased. The synthesized polyurethane has characteristic absorption of urethane functional group and cross link. The increasing of incubation time can decrease biodegradability of polyurethane. The mass loss of polyurethane from SBO-PEG400-MDI has the higher. Biodegradation can disappear urethane group and decrease crystallinity of polyurethane. Key words: biodegradation, mass loss, crystallinity, polyurethane